An academic results analysis of a first year interdisciplinary project approach to industrial and management engineering education - Fernandes, Sandra (2009)
This paper presents an analysis of academic results of first year Industrial Management and Engineering students, achieved either in a PLE (Project-led Education) or in a non PLE teaching and learning approach. Data collected focuses on students’ grades, including continuous and summative assessment results of four different courses, from the academic year 2006/2007 to 2008/2009. The evaluation indicators used are the ratio of students assessed and those enrolled in the course, the ratio of students approved and those enrolled in the course, the ratio of students approved and those assessed in the course, the arithmetic mean and the standard deviation of student grades. Findings suggest that PLE students, in average, have better results than the non PLE students at all courses and for the three academic years analyzed. However, these results need to be understood in a broader perspective which includes other variables such as student background, student engagement of given tasks, etc. which are beyond the scope of this paper.